Espectroscopia vibracional em cristais de L-histidina - Pinheiro, Gardenia de Sousa (2009)
In this work, we have investigated L-histidine (C6H9N3O2) crystals through Raman spectroscopy in the spectral region 30 - 3450 cm−1 with temperature (30 - 428 K) and pressure (0,1 - 7,0 GPa) variations. Under low temperature conditions (30 K ≤ T ≤ 291 K) it was observed that the L-histidine crystal undergoes a conformational phase transition at 170 K. This conclusion is based on the temperature behavior of Raman bands associated with CO− 2 and NH+ 3 vibrations. Under high temperature conditions (300 K≤T≤428 K) the mode frequency of most of the peaks appearing on the Raman spectra of L-histidine present harmonic behavior up to the decomposition, at 428 K. High pressure Raman measurements were performed on two crystalline form of L-histidine: pure L-histidine and L-histidine hydrochloride monohydrated (C6H9N3O2·HCl·H2O). It was not observed any clear evidence for structural phase transition undergone by L-histidine up to 7,01 GPa. On the other hand, for L-histidine hydrochloride monohydrate, wich was investigated in the spectral range 0,7 - 7,5 GPa, we have obtained evidence that the crystal undergoes a reversible phase transition at approximately 2,7 GPa.